2018
DOI: 10.1007/978-3-030-03424-5_2
|View full text |Cite
|
Sign up to set email alerts
|

DReAM: Dynamic Reconfigurable Architecture Modeling

Abstract: Modern systems evolve in unpredictable environments and have to continuously adapt their behavior to changing conditions. The "DReAM" (Dynamic Reconfigurable Architecture Modeling) framework, has been designed for modeling reconfigurable dynamic systems. It provides a rule-based language, inspired from Interaction Logic, which is expressive and easy to use encompassing all aspects of dynamicity including parametric multi-modal coordination with creation/deletion of components as well as mobility. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The model is inspired from the BIP coordination language. It has been studied and implemented in two formalisms, one declarative and another imperative [3,4,5].…”
Section: A Computational Model For Autonomous Systems 21 a System Arc...mentioning
confidence: 99%
See 1 more Smart Citation
“…The model is inspired from the BIP coordination language. It has been studied and implemented in two formalisms, one declarative and another imperative [3,4,5].…”
Section: A Computational Model For Autonomous Systems 21 a System Arc...mentioning
confidence: 99%
“…Self-organization is the ability to adapt coordination rules to changing system dynamics. We have shown that all these types of architectures can be formalized as operators taking as arguments arbitrary numbers of instances of agent and objects types [3,4,5]. We badly need theory for studying their properties in a compositional manner.…”
Section: Architecture Complexitymentioning
confidence: 99%
“…We characterize the complexity of architectures by the degree to which all these attributes may dynamically change and be organized, as illustrated in Figure 5. This classification distinguishes five types of architectures and has been carried out based on technical criteria presented in [12,13]. 5.…”
Section: Architecture Complexity -Self-organizing Architecturesmentioning
confidence: 99%